Paracentral Acute Middle Maculopathy and Nonischemic Central Retinal Vein Obstruction in a Young Patient with Protein C Deficiency - Mojtaba Abrishami; Seyedeh Maryam Hosseini; Nasser Shoeibi; Hamid Reza Heidarzadeh (Case Reports in Ophthalmological Medicine, 2022)
Purpose. To report a case of protein C deficiency with paracentral acute middle maculopathy (PAMM) and nonischemic central retinal vein obstruction (NI-CRVO). Case Report. A previously healthy twenty-one-year-old male was referred with sudden-onset, painless, unilateral paracentral scotomata in the right eye for a week. His uncorrected visual acuity was 20/20 in both eyes. In fundus examination of the right eye, mild venous tortuosity, retinal hemorrhages, and a gray-white opacity in the papillomacular bundle were observed. In the macular spectral-domain optical coherence tomography images, a hyperreflective band was noticed at the level of the inner nuclear layer, indicating PAMM. Fundus appearance and fluorescein angiography findings indicated NI-CRVO diagnosis made. The systemic and laboratory evaluations disclosed a protein C deficiency. Conclusion. In this report, in a healthy young male, combined PAMM and NI-CRVO showed to be the cause of blurred vision in the setting of protein C deficiency.